Managing risk and performance : a guide for government decision makers - Stanton, Thomas H., 1944-; Webster, Douglas W., 1948- (Hoboken, New Jersey : John Wiley and Sons, 2014)
'Discover analytical tools and practices to help improve the quality of risk management in government organizationsFederal agencies increasingly recognize the importance of active risk management to help ensure that they can carry out their missions. High impact events, once thought to occur only rarely, now occur with surprising frequency. Managing Risk in Government Agencies and Programs provides insight into the increasingly critical role of effective risk management, while offering analytical tools and promising practices that can help improve the quality of risk management in government organizations. Includes chapters that contribute to the knowledge of government executives and managers who want to establish or implement risk management, and especially Enterprise Risk Management (ERM), in their agencies Features chapters written by federal risk managers, public administration practitioners, and scholars Showing government officials how to improve their organization's risk management capabilities, Managing Risk in Government Agencies and Programs meets a growing demand from federal departments and agencies that find themselves increasingly embarrassed by risky events that raise questions about their ability to carry out their missions'--
Machine generated contents note: Foreword Preface Part One: Introduction and Overview Chapter 1 Managing Risk of Federal Agencies and their Programs Through Enterprise Risk Management (ERM) (Thomas H. Stanton) I. Risk Management as an Essential Part of Federal Management II. Risk Management as an Integral Part of Good Decision-making III. The Unique Challenges of Managing a Government Agency IV. Establishing Effective Risk Management V. Managing Risk in Government Agencies: Overview of the Book References Chapter 2 The Need for Effective Risk Management (Douglas W. Webster) I. Defining Risk II. The Source of Uncertainty: Change III. Risk and Reward IV. The Risk Management Process V. The Essence of Organizational Success: Stakeholder Value VI. The Role of Information Technology (IT) in Risk Management VII. The Importance of Organizational Change Management VIII. Pulling It All Together IX. Conclusion References Chapter 3 Introduction to Risk Management for Government Managers (Thomas H. Stanton) I. Fitting Risk Management into an Organization II. Promising Practices in Risk Management III. Observations about Risk Management in Government: What Works and What Doesn't VI. Conclusion References Chapter 4 Risk Management and Challenges of Managing in the Public Sector (Paul L. Posner and Thomas H. Stanton) I. Unique Risk Management Challenges of Public Programs II. Third Party Governance: The Challenge of Managing Risk Across Organizational III. Goal-Setting, Accountability, and Prioritization of Risks: Special Challenges Facing Government Managers IV. Concluding Observations References Chapter 5 Creating and Keeping Your Options Open - It's Fundamental (Brian Barnier) The Real World is Rarely Simple and Stable Systems Set the Stage Managing More Easily - Options in Time Examples of Options in Time in Practice Conclusion Key Points References Part Two: Moving Towards ERM Chapter 6 Introduction to Enterprise Risk Management (ERM) for Government Managers (Douglas W. Webster) I. Shortcomings of Traditional Risk Management II. The impact of managing risk within silos--a case study III. The Maturation of Traditional Risk Management into ERM IV. Key Principles of ERM V. What ERM is Not VI. The Payoff VII. Summary References Chapter 7 Implementation of Enterprise Risk Management at the Office of Federal Student Aid of the U.S. Department of Education (Fred Anderson and Cynthia Vitters) I. Overview of FSA II. Initial Implementation of ERM at FSA III. Initial Activities and Challenges in Implementing ERM at FSA IV. Expanding the ERM Program - A Change in FSA's Business Model V. Key Considerations and Challenges When Implementing the Expanded ERM Program at FSA VI. Conclusion References Acknowledgments Chapter 8 Integrating ERM into Strategic Planning and Resource Management (Jeffrey Stagnitti) I. Context II. ERM and Strategy III. ERM and Resource Management IV. Conclusion Chapter 9 Building ERM (Enterprise Risk Management) into Agency Processes and Culture (John Fraser) I. Building a shared understanding of risks through conversations II. The Key ERM Techniques III. Improved Decision Making and Prioritization IV. Conclusion References For Further Reading Appendix: Hydro One Inc. Enterprise Risk Management Policy Part Three: Special Topics in Risk Management and Response Chapter 10 Risk Management and the Dynamics of Downsizing (Thomas H. Stanton) I. Dynamics of Protracted Budget Controversy and the Risk and Uncertainty this Creates II. Long-Term Budget Cuts and the Risks they Create III. The Role of Risk Management in Reducing Chances of a Major Mishap IV. Strengthening the Ability of Agencies to Make Better Decisions to Deal with Budget Uncertainty and Budget Cuts V. Conclusion References Chapter 11 Managing Reputational Risk (Gary L. Glickman) I. What is Reputational Risk and What Does it Mean to Government? II. What Determines Reputation and How Can Government Address these Factors? III. External Influences on Reputation IV. Consequences of Reputational Loss for Government Organizations V. Reputational Risk Mitigation VI. Conclusion References Chapter 12 Risk Management and Decision Making Lessons from the Financial Crisis for Federal Managers (Thomas H. Stanton) I. The Financial Crisis: How it Emerged, What Happened, and the Costs II. Decision Making at Firms that Failed: Common Shortcomings III. Decision Making at Firms that Succeeded; The Importance of Culture IV. Lessons in Governance, Risk Management, and Decision Making V. Conclusions References Part Four: Conclusion Chapter 13 Effective Enterprise Risk Management: Mapping the Path Forward (Douglas Webster) I. Recommendations II. Conclusion References For Further Information For Further Reading About the Editors About the Contributors Index .
Includes bibliographical references and index.
Keywords: Risk management; Government executives